Machine Learning Approaches in Financial Analytics - Maglaras, Leandros A.; Das, Sonali; Tripathy, Naliniprava; Patnaik, Srikanta (Intelligent Systems Reference Library, 2024)
XX, 483 p. 105 illus., 88 illus. in color.